Secret manipulations language and context in Africa - Storch, Anne. (Oxford : Oxford University Press, 2011)
This book addresses a specific form of language change: deliberate manipulations of a language by its speakers. These manipulations are based and depend on cultural and social contexts; they are often considered to be secret and are at the same time expressions of difference and power.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Linguistic change -- Africa; Africa -- Languages